2016
DOI: 10.1111/famp.12272
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Observed Parent Socialization of Coping and Skin Conductance Level Reactivity to Childhood Adjustment

Abstract: This research examined the longitudinal association between parent socialization of coping and child adjustment, as well as the moderating role of children's skin conductance level reactivity (SCLR). Participants were a community sample of children (n = 64, M age = 9.02, 54.5% females, 93.2% Caucasian) and their parent(s). Parent coping suggestions were observed while their child engaged in a stressful challenge task, during which the child's SCLR, a measure of children's physiological reactivity to stress, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 42 publications
1
7
0
1
Order By: Relevance
“…This procedure builds upon prior work by allowing us to capture coping suggestions in real time with a task that is developmentally appropriate for middle childhood samples. Using this paradigm, we found that secondary control engagement suggestions predicted more internalizing symptoms over time and disengagement suggestions predicted more externalizing symptoms over time among youth with heightened physiological reactivity (Stanger et al, 2017), which supports the predictive validity of this method.…”
Section: Socialization Of Copingsupporting
confidence: 62%
See 3 more Smart Citations
“…This procedure builds upon prior work by allowing us to capture coping suggestions in real time with a task that is developmentally appropriate for middle childhood samples. Using this paradigm, we found that secondary control engagement suggestions predicted more internalizing symptoms over time and disengagement suggestions predicted more externalizing symptoms over time among youth with heightened physiological reactivity (Stanger et al, 2017), which supports the predictive validity of this method.…”
Section: Socialization Of Copingsupporting
confidence: 62%
“…For children who are highly frustrated or aroused during a stressful task, parent encouragement to disengage could be beneficial in other domains of adjustment. In this sample, Stanger et al (2017) found that disengagement suggestions predicted fewer externalizing problems over time, but only among youth with high physiological arousal during the mirror-tracing task. Thus, disengagement suggestions should not be interpreted as uniformly maladaptive.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In a middle childhood sample, Boyce et al (2006) found that father involvement interacted with maternal depression and autonomic reactivity (indexed via mean arterial blood pressure), such that youth with low father involvement, high maternal depression, and high blood pressure reactivity demonstrated the most severe mental health symptoms. Other studies of middle childhood have found that parent depressive symptoms predicted internalizing symptoms, externalizing symptoms, and social problems in those with high SCLR (Cummings, El-Sheikh, Kouros, & Keller, 2007), observed parent disengagement coping suggestions predicted less externalizing problems among those with high SCLR (Stanger, Abaied, Wagner, & Sanders, 2016), and harsh parenting predicted externalizing problems among boys with low SCLR (Erath, El-Sheikh, & Cummings, 2009).…”
Section: Maternal Involvement and Psychological Control In Adolescencementioning
confidence: 88%